Exploratory analyses of relief and development operations using social networks. (December 2016) - Urrea, Gloria; Villa, Sebastián; Gonçalves, Paulo
Abstract: We use social networks to explore how structural factors affect humanitarian organizations' performance in relief and development operations. Analyses of two recent humanitarian disasters show that having pre-established partnerships among implementers, a central coordinator, high connectivity, and few structural holes facilitates coordination and improves performance. Similarly, cost efficiency analyses of 757 development programs reveal that (i) high performance of donors and beneficiaries is positively related to the amount of implementers they interact with, and (ii) programs connected by common actors are more cost efficient. Finally, short path lengths and frequent connections among actors or programs improve performance in humanitarian operations. Highlights: Pre-established partnerships among implementers may lead to better relief responses. High network closure and few structural holes allow for better information flow. Donors' cost efficiency is positively correlated with the number of implementers. Development programs connected by common actors may lead to better performance. Short path lengths and frequent connections improve humanitarian performance.